Case report: Solitary fibrous tumor of the paracervical uterus combined with vaginal wall adenocarcinoma - Zhang, Xiaowei; Chen, Jun; Du, Junqiang; Ying, Jiajia (Frontiers in Medicine, 2024)
Background Solitary fibrous tumors are rare mesenchymal tumors that typically occur in the pleura. Solitary fibrous tumors of the uterine cervix are uncommon. We report the first case of a patient who underwent total hysterectomy for vaginal wall adenocarcinoma and was found to have a concurrent solitary fibrous tumor in the paracervical-uterus. Case presentation A 51-year-old woman was admitted to our hospital due to contact bleeding. A gynecological examination revealed nodules of 3.0 × 1.0 cm on the vaginal wall, and a colposcopy with biopsy revealed adenocarcinoma of the vaginal wall. After the recommended staging examinations, the patient underwent total hysterectomy, double adnexectomy, pelvic lymph node dissection, and vaginal wall resection. During surgery, a nodule measuring approximately 2 × 2 cm was found in the middle of the mass in the left paracervical region. Subsequent postoperative histopathological examination confirmed an solitary fibrous tumor of the uterine cervix with adenocarcinoma of the vaginal wall. The patient was followed up for 46 months after hospitalization, and no recurrence or distant metastases were observed. Conclusion In rare cases, solitary fibrous tumors may form large masses in the cervical or vaginal wall. They can easily be misdiagnosed as benign or malignant cervical tumors before and during surgery. Postoperative pathology and immunohistochemistry are helpful for diagnosis. Most solitary fibrous cervical tumors are benign, occasionally with low malignant potential, and surgical treatment is feasible and effective.